INVESTIGATING THE PREVALENCE OF HBV AMONG BLOOD DONORS IN THE CENTRAL BLOOD BANK OF KABUL CITY, AFGHANISTAN 2022 - Mohammad Bashir Shahi; Razia Miri; Sughra Alizada; Abdullah Rezaie (Web of Journals Publishing, 2023)
Introduction: Hepatitis B Virus (HBV) is one of the most common hepatitis in humans. These viral infections lead to dysfunction of the liver and sometimes even lead to liver cancer. HBV is also transmitted through blood, so blood must first be evaluated to be free from HBV during blood transfusion. The prevalence of HBV among blood donors is considered one of the risk factors for transmission of this virus and requires caution. Aim and methods: The aim of writing this thesis is to investigate the prevalence of HBV among blood donors in the central blood bank, taking into account age, gender, marital status, residence, and history of blood donation. This study is a prospective study, the required data of which was collected from the 6 months of 2022, from blood donors in the central blood bank of Kabul city. Results: According to the findings of this study, the prevalence of HBV among blood donors in the central blood bank of Kabul, out of 6406 blood donors, 90 positive cases (1.4%) have been observed. The highest incidence of HBV was recorded in the age group of 18 to 28 years with 32 cases (35.3%). Out of 90 registered cases of HBV, 88 of them were related to the male category, and the highest recorded statistics were reported among people with married status (83.3%). Most of the people with HBV are residents of Kabul City (70%) and the majority of HBV-positive cases have been registered without a history of donating blood (76.6%). Conclusion: The prevalence of HBV among blood donors in the central blood bank is relatively high, and it should be prevented by observing the principles of hygiene and public awareness about this disease.
Keywords: HBV infection, Blood donor, and Central Blood Bank of Kabul, Afghanistan.